2017
DOI: 10.5045/br.2017.52.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin: clinical updates and practical guidance

Abstract: Brentuximab vedotin (BV), a potent antibody-drug conjugate, targets the CD30 antigen. Owing to the remarkable efficacy shown in CD30-positive lymphomas, such as Hodgkin's lymphoma and systemic anaplastic large-cell lymphoma, BV was granted accelerated approval in 2011 by the US Food and Drug Administration. Thereafter, many large-scale trials in various situations have been performed, which led to extensions of the original indication. The aim of this review was to describe the latest updates on clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 95 publications
2
39
0
3
Order By: Relevance
“…Other ADCs that have been approved are brentuximab vedotin (Adcetris; Seattle Genetics, Inc.; CD30 targeted; ref. 13) and inotuzumab ozogamicin (Besponsa; Pfizer; CD22 targeted; ref. 14), which were approved for hematologic malignancies, and trastuzumab emtansine (Kadcyla; Genentech; HER2 targeted), which was approved for breast cancer (15).…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Other ADCs that have been approved are brentuximab vedotin (Adcetris; Seattle Genetics, Inc.; CD30 targeted; ref. 13) and inotuzumab ozogamicin (Besponsa; Pfizer; CD22 targeted; ref. 14), which were approved for hematologic malignancies, and trastuzumab emtansine (Kadcyla; Genentech; HER2 targeted), which was approved for breast cancer (15).…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
“…Clear clinical benefits have been demonstrated with all 4 approved ADCs; however, each has reported toxicity profiles that are specific to its cytotoxic warhead and, therefore, they cannot be differentiated from standard-of-care chemotherapies (13)(14)(15) in terms of safety. Regardless of the obstacles, there is intense interest in developing ADCs-approximately 80 ADC candidates are reportedly in clinical development, with nearly 600 clinical trials ongoing-and it is likely that several new ADCs will be approved over the next few years ( Fig.…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For brentuximab vedotin, a cathepsin cleavable valine-citrulline linker was chosen, as it met these criteria and, moreover, allowed for better water solubility and satisfactory pharmacokinetics of the drug (Doronina et al, 2003). Recognition showed a reduced toxicity by nearly 1,000 times, thus displaying an antigen-dependent effect (Francisco et al, 2003;Yi, Kim, & Kim, 2017 (Younes, 2011). Furthermore, Phase II trials in patients with Hodgkin's lymphoma and ALCL showed ORR of 73% (with 32% complete responses) and 86% (with 57% complete responses) respectively (Younes, Yasothan, & Kirkpatrick, 2012).…”
Section: Warhead Drugs (Brentuximab Vedotin Adcetris): Special Delmentioning
confidence: 99%
“…Brentuximab vedotin (BV) is a chimeric IgG1 anti-CD30 antibody–drug conjugated by a protease-cleavable linker to the microtubule-disrupting agent monomethyl auristatin E that has shown impressive antitumor activity in both HL and ALCL. 5 Targeted delivery of monomethyl auristatin E to CD30 expressing tumor cells is the primary mechanism of action of BV. Additional mechanisms of tumor cell death that may contribute to the clinical activity of this drug include antibody-dependent cellular phagocytosis, immunogenic cell death, and the bystander effect.…”
Section: Introductionmentioning
confidence: 99%